Accurate diagnosis of occlusal carious lesions - a stereo microscope evaluation of clinical diagnosis - Grossman, E. S.; Cleaton-Jones, P. E.; Côrtes, D. F.; et al (My University, 2002)
This study was undertaken to validate the caries status of 214 teeth by serial sectioning and microscopy after caries diagnosis using four methods. Two hundred and fourteen extracted human teeth with varying degrees of caries were mounted in the jaws of nine training manikins. All tooth surfaces were examined and recorded for caries by four dentists using bitewing radiographs, fibre-optic transillumination (FOTI), mirror alone and a mirror and sharp probe on two separate occasions. Thereafter the teeth were serially sectioned and assessed microscopically for depth of caries lesion on a graded score of 0-7. This report assessed the diagnostic outcome of 2,183 observations for occlusal surfaces. Sound diagnoses predominated over unsound until caries was present in the inner half of dentine. Specificity was between 90% and 95% and sensitivity 26% and 50% depending on which diagnostic method was used and where the sound/unsound threshold was set. Negative and positive predictive values were similarly influenced and varied between 53% and 80% and 73% and 90%, respectively. Probit analysis showed no significant differences (P < 0.05) between examiners and diagnostic methods. Diagnosis of occlusal caries undertaken in an in vitro simulated clinical situation is inaccurate until the caries lesion extends deep into the dentine no matter which of the four methods was used.
KIM
Keywords: Dentin; Microscopy; Dental Caries/diagnosis